Exploring dietary changes in an interdisciplinary intervention trial: Application of a dietary guidelines food composition database. Issue 2 (29th July 2020) - Zoszak, K.; Neale, E.; Tapsell, L.; Probst, Y.
Abstract: Background: Consumption of food groups aligning with dietary guidelines is advised for obesity management and was used in a recent lifestyle intervention trial, the Health Track study. We have conducted a number of dietary pattern analyses on this trial but, with recent access to the new Australian Dietary Guidelines (ADG) food composition database, we can now assess ADG adherence, with the advantage of categorising mixed dishes. The present study aimed to compare changes over time in consumption of ADG food groups. Methods: Secondary analysis of baseline and three‐month diet history data was conducted. Participants received individualised dietary advice ( I ), individualised dietary advice plus 30 g of walnuts per day (IW) or usual care ( C ). The ADG database was used to determine food group servings with changes in five food groups used as a measure of dietary quality. Results: Fruit and vegetable intakes increased in the IW (+0.4 and +1.1 serves, P < 0.05) and I (+0.5 and +0.4 serves, P > 0.05) arms. Consumption of meat/protein foods increased in the IW arm (+0.3 serves, P > 0.05) but decreased in the I and C arms (both − 0.4 serves, P < 0.05). Consumption of grains and milk/alternatives decreased in all study arms ( P < 0.05). Greater improvements in grain and dairy food quality were observed in the intervention arms. Conclusions: The ADG database enabled ADG specific food group analysis, addressed food quality and showed the HealthTrack intervention increased adherence to dietary guidelines compared to usual care. Abstract : Applying the Australian Dietary Guidelines Database to dietary assessment data of an interdisciplinary intervention study enabled the reported food items to be deconstructed into their component food groups. These data provided a useful measure of the changed dietary quality between intervention time points.